2021
DOI: 10.1016/j.clinimag.2021.03.032
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric radiologic manifestations of COVID-19

Abstract: Purpose While full description of pediatric COVID-19 manifestations is evolving, children appear to present less frequently, and often display a less severe disease phenotype. There is correspondingly less data regarding pediatric radiologic findings. To describe the imaging findings of pediatric COVID-19, we evaluated the radiologic imaging of the initial patient cohort identified at our institution. Methods In this IRB approved study, all patients at our institution a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Another COVID-positive patient had abdominal pain, fever, vomiting, and hypotension. Abdominal CT showed minimal lymphadenopathy and traces of free fluid in the abdomen as well as minimal clouding of the basilar pulmonary lung glass (44) . Meyer et al draw attention to the possible association between COVID-19 and appendicitis.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Another COVID-positive patient had abdominal pain, fever, vomiting, and hypotension. Abdominal CT showed minimal lymphadenopathy and traces of free fluid in the abdomen as well as minimal clouding of the basilar pulmonary lung glass (44) . Meyer et al draw attention to the possible association between COVID-19 and appendicitis.…”
Section: Discussionmentioning
confidence: 97%
“…Polites and Azarow (2020) (37) With comparable outcomes for operative and non-operative management of uncomplicated appendicitis, hospitals must consider capacity and resources in determining the best course of action Tankel et al (2020) (38) The significant decrease in the number of patients admitted with acute appendicitis during the onset of COVID-19 possibly represents successful resolution of mild appendicitis treated symptomatically by patients at home Saleem et al (2020) (39) More than half of the patients had perforated appendix, which was the highest percentage observed in the group of patients during the period of two months Mehl et al (2021) (40) COVID-19 children requiring surgery have a favourable postoperative course and short-term outcomes compared to the reported adult experience Rohani et al (2021) (41) COVID-19 has many different and mysterious presentations. Gastrointestinal manifestations are among the most important, common presentations Hwang et al (2021) (42) Laboratory criteria, specifically low-normal white blood cell count and thrombocytopenia, appear to be of high relevance in differentiating MIS-C from acute appendicitis, even when the appendix is radiologically dilated Gerall et al (2021) (43) A rash as well as tachycardia and/or hypotension and elevated inflammatory markers out of proportion to the amount of inflammation seen on imaging should be used to differentiate a typical surgical abdomen from MIS-C and prompt testing for active SARS-CoV-2 infection as well as antibodies Romberg et al (2021) (44) CT of COVID-positive patients with severe abdominal pain showed lymphadenopathy, mild thickening of the intestinal wall, and mesenteric oedema Meyer et al (2021) (45) We encourage consideration of testing for SARS-CoV-2 in paediatric patients with severe gastrointestinal symptoms to inform about strategies to alleviate transmission and possible complications due to unnecessary surgical treatment Rico Espiñeira et al (2021) (46) Gastrointestinal symptoms can be the primary manifestation of the new coronavirus infection, which simulates an acute abdomen with a potentially unfavourable evolution. For an accurate diagnosis to be achieved, a good clinical record and a comprehensive physical exploration, as well as complementary tests in search of characteristic findings of COVID-19, should be carried out Jackson et al (2020) (47) MIS-C should be considered in patients with prominent gastrointestinal symptoms and a history of recent SARS-CoV-2 exposure or infection.…”
Section: Discussionmentioning
confidence: 99%
“…The most common CT abnormalities described in pediatric COVID-19 pneumonia are multiple ground-glass opacities, with or without consolidation, which can be subpleural/peripheral or central in location [ 45 48 , 51 , 54 , 56 , 63 72 ] (Figs. 4 and 5 ).…”
Section: Imaging Findings In Acute Coronavirus 2019mentioning
confidence: 99%
“…Interstitial-type opacities and small airway-type findings, such as bronchial wall thickening, septal thickening and tree-in-bud nodules, have been described as highly frequent in some studies, but uncommon in other studies [ 45 , 51 , 54 , 64 , 66 68 ]. As with chest radiography, pleural effusions are not usually seen, and when present are typically small in size [ 45 , 51 , 56 , 67 ]. An increased risk for pulmonary embolism in COVID-19-infected adults has been well described, but thus far it appears to be uncommon in children [ 45 , 68 , 73 , 74 ].…”
Section: Imaging Findings In Acute Coronavirus 2019mentioning
confidence: 99%
See 1 more Smart Citation